Fiscal stimulus and distortionary taxation - Thorsten Drautzburg; Harald Uhlig (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
We quantify the fiscal multipliers in response to the American Recovery and Reinvestment Act (ARRA) of 2009. We extend the benchmark Smets-Wouters (Smets and Wouters, 2007) New Keynesian model, allowing for credit-constrained households, the zero lower bound, government capital and distortionary taxation. The posterior yields modestly positive short-run multipliers around 0.52 and modestly negative long-run multipliers around -0.42. The multiplier is sensitive to the fraction of transfers given to credit-constrained households, the duration of the zero lower bound and the capital. The stimulus results in negative welfare effects for unconstrained agents. The constrained agents gain, if they discount the future substantially.
Keywords: E62; E63; E65; H20; H62; 330; Fiscal Stimulus; New Keynesian model; liquidity trap; zero lower bound; fiscal multiplier; Konjunkturpolitik; Finanzpolitik; Multiplikator; Steuerprogression; Zinspolitik; Verschuldungsrestriktion; Schätzung; USA